2016
DOI: 10.1016/j.expneurol.2015.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Altered long non-coding RNA transcriptomic profiles in brain microvascular endothelium after cerebral ischemia

Abstract: The brain endothelium is an important therapeutic target for the inhibition of cerebrovascular dysfunction in ischemic stroke. Previously, we documented the important regulatory roles of microRNAs in the cerebral vasculature, in particular the cerebral vascular endothelium. However, the functional significance and molecular mechanisms of other classes of non-coding RNAs in the regulation of cerebrovascular endothelial pathophysiology after stroke are completely unknown. Using RNA sequencing (RNA-seq) technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
138
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(147 citation statements)
references
References 67 publications
(117 reference statements)
4
138
0
Order By: Relevance
“…Wu et al found that lncRNA-N1LR promoted neuroprotection against ischemic stroke by inhibiting p53 phosphorylation and served as a potential target for therapeutic intervention following ischemic brain injury [35]. In the present study, we found that MALAT1 was significantly up-regulated in MCAO mice and cortical neurons subjected to OGD, consistent with a previous study [17]. More importantly, MALAT1 down-regulation dramatically restrained the conversion of LC3-I to LC3-II and Beclin1 level in vitro and in vivo , indicating MALAT1 down-regulation suppressed autophagy in ischemic stroke.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Wu et al found that lncRNA-N1LR promoted neuroprotection against ischemic stroke by inhibiting p53 phosphorylation and served as a potential target for therapeutic intervention following ischemic brain injury [35]. In the present study, we found that MALAT1 was significantly up-regulated in MCAO mice and cortical neurons subjected to OGD, consistent with a previous study [17]. More importantly, MALAT1 down-regulation dramatically restrained the conversion of LC3-I to LC3-II and Beclin1 level in vitro and in vivo , indicating MALAT1 down-regulation suppressed autophagy in ischemic stroke.…”
Section: Discussionsupporting
confidence: 82%
“…Accumulating evidence reveals that MALAT1 is up-regulated in many solid tumors and associated with cancer metastasis and recurrence [16]. More interestingly, MALAT1 was reported to be highly expressed in an in vitro mimic of ischemic stroke conditions [17]. However, the role of MALAT1 in ischemic stroke and its underlying mechanism have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…It has become increasingly important to elucidate the molecular mechanisms of acute cerebral ischemia-related neuronal injury [26]. As we have discussed previously, there are studies which have reported that cerebral miRNA and lncRNAs control epigenetic silencing or activation in mammal also get altered due to cerebral ischemia [27-29]. Moreover, long non-coding RNAs (LncRNAs), also go through changes in the post-stroke brain [30].…”
Section: Discussionmentioning
confidence: 99%
“…In HeLa cells, it has been shown to control the HIF-1α axis under hypoxic conditions in a positive feedback loop [20]. After ische­mic stroke, it regulates gene expression in cerebrovascular endothelial cells [21, 22], where it is proposed to protect against hypoxia-reperfusion-induced apoptosis [23]. MALAT1 has been of interest as a therapeutic target after its downregulation was found to suppress ischemic injury and autophagy in vitro and in vivo, which makes its strong upregulation in our data of particular interest [24].…”
Section: Discussionmentioning
confidence: 99%